(3TQM CHjGJ TQM GdcGajIs - (3YjSi Hf CMeO GdTQhGfjs; (3GdNHjUj , eMeO Hf CHj HcQ Hf eMQR, TeS GdOjf GdNHjUj,J (B731 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdfMh ajbhd GdYHO GdabjQ YjSi Hf CMeO GdTQhGfj(B: (3deG cGf TQM GdcGajI s
(3BNQgG (B:s
(3hGdYQYQI dYHI GdUHjGf haj GdCUd gj GdJMQjc hYQYGQ eYQhd Yfg eHfj Ydi GdcSQ s
(3HgG fXGe GdJYbjHIs
(3TQM GdcGajI GdeSei HGdehTMs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B116s
Keywords: (3GdfMhs